Global Study of Social Odor Awareness. (27th June 2018) - Sorokowska, Agnieszka; Groyecka, Agata; Karwowski, Maciej; Frackowiak, Tomasz; Lansford, Jennifer E; Ahmadi, Khodabakhsh; Alghraibeh, Ahmad M; Aryeetey, Richmond; Bertoni, Anna; Bettache, Karim; Blumen, Sheyla; Błażejewska, Marta; et al.
Abstract: Olfaction plays an important role in human social communication, including multiple domains in which people often rely on their sense of smell in the social context. The importance of the sense of smell and its role can however vary inter-individually and culturally. Despite the growing body of literature on differences in olfactory performance or hedonic preferences across the globe, the aspects of a given culture as well as culturally universal individual differences affecting odor awareness in human social life remain unknown. Here, we conducted a large-scale analysis of data collected from 10 794 participants from 52 study sites from 44 countries all over the world. The aim of our research was to explore the potential individual and country-level correlates of odor awareness in the social context. The results show that the individual characteristics were more strongly related than country-level factors to self-reported odor awareness in different social contexts. A model including individual-level predictors (gender, age, material situation, education, and preferred social distance) provided a relatively good fit to the data, but adding country-level predictors (Human Development Index, population density, and average temperature) did not improve model parameters. Although there were some cross-cultural differences in social odor awareness, the main differentiating role was played by the individual differences. This suggests that people living in different cultures and different climate conditions may still share some similar patterns of odor awareness if they share other individual-level characteristics.